Role of Law Students in Providing Legal Literacy through Street Law - Leni Widi Mulyani (The Indonesian Journal of International Clinical Legal Education, 2019)
Clinical Legal Education (CLE) is a program designed to develop soft skills among law students, enabling them to graduate with the competencies and social commitment necessary to assist others. The primary beneficiaries of this program are poor and marginalized communities who require support in accessing justice. CLE encompasses various activities, and one of the clinics developed by the Faculty of Law, Pasundan University Bandung, focuses on providing legal aid through legal learning and knowledge-sharing for those in need. Through this initiative, students gain practical exposure while contributing to the empowerment of vulnerable groups.